1993
DOI: 10.1111/j.1365-2249.1993.tb03345.x
|View full text |Cite
|
Sign up to set email alerts
|

ANCA and associated diseases: immunodiagnostic and pathogenetic aspects

Abstract: The past decade has seen an explosion of data on the new group of autoantibodies known collectively as ANCA (anti-neutrophil cytoplasmic antibodies). ANCA are specific for granule proteins of granulocytes and monocytes and induce distinct fluorescence patterns, e.g. the cytoplasmic (classic) cANCA and the perinuclear pANCA. cANCA is induced by antibodies directed against Proteinase 3 (PR3; PR3-ANCA) in about 90% of all ANCA-positive sera, and pANCA is induced by antibodies against myeloperoxidase (MPO; MPO-ANC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0
11

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(60 citation statements)
references
References 102 publications
0
46
0
11
Order By: Relevance
“…[5][6][7][8] Although antibodies to PR3 and MPO play a pivotal role in AAV, understanding the regulation and consequences of dysregulation of the genes encoding PR3 and MPO may provide unique insight into the disease process.…”
mentioning
confidence: 99%
“…[5][6][7][8] Although antibodies to PR3 and MPO play a pivotal role in AAV, understanding the regulation and consequences of dysregulation of the genes encoding PR3 and MPO may provide unique insight into the disease process.…”
mentioning
confidence: 99%
“…The ANCA titre was measured by a standard indirect immunofiuorescence test (IIF) on ethanol-fixed human neutrophils [22,23]. Briefly, ethanol-fixed human neutrophils were incubated with patient sera at increasing dilutions, bound antibodies were stained with fluorescein-conjugated rabbit antihuman IgG and read by UV-microscopy.…”
Section: Determination Of Ancamentioning
confidence: 99%
“…At one time tubercuiosis was thought to underiie TA, but tiire is no convincing proof, Whiie a high percentage of patients give a positive tubercuiin sidn test, this may oniy indicate increased susceptibiiity to infection in societies where tubercuiosis is common. The diagnostic vaiueof ANCA and its pathogenic impiications proved to beparticuiariy important in systemic vascuiitides such as Wegener" s granuiomatosis (WG), microscopic polyarteritis (mPAN) and the cioseiy related pauci immune necrotizing and crescentic glomerulonephritis [1,2,3]. As soon as ANCA testing became widely avaiiable.…”
mentioning
confidence: 99%
“…In addition, it has been shown that the IgG fraction of IVIg that is retained on F('db')^ fragments frt>iTi IVIg by affinity chromatography mainly contains autoantibodies 12], indicating that natural autoantibodies are particularly prone to idiotypic interactions. Studies on the expression and control of the natural autoreactive IgG repertoire showed that iti healthy subjects serum IgG autoreactivity towards a wide spectrumof autoantigens is significantly lower than that of purifiedIgG [3]. The observation thatlgG-depleted serum andpurifiedlgM are capable of inhibiting the binding of IgG to many autoantigens and that IgM can bind to F(ab')j fragments of IVIg [3] indicate that the functional antiUxly network includes not only V region interactions between IgG molecules, but also between IgM and IgG.…”
mentioning
confidence: 99%
See 1 more Smart Citation